HUBUNGAN KEPEMIMPINAN DENGAN KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN PASAMAN - Harry Mulyadi (Jurnal Bahana Manajemen Pendidikan, 2014)
The purpose of this resear is to see the information abuot the correlation between The leadership and employee’s performance. Population are 70 employees and The 41employees were taken as sample. The Research instrumen is question with likert scale which its validity and realibity has been tested. The data bas analisis pusing product momment correlatio  betwen The leadership Ana Education (dinas)’s employees performance. Keyword: leadership and performance